Growing up communist in the Netherlands and Britain : childhood, political activism, and identity formation. - Weesjes, Elke (Amsterdam University Press, 2021)
This book documents communists' attempts, successful and otherwise, to overcome their isolation and to connect with the major social and political movements of the twentieth century. Communist parties in Britain and the Netherlands emerged from the Second World War expecting to play a significant role in post-war society, due to their domestic anti-fascist activities and to the part played by the Soviet Union in defeating fascism. The Cold War shattered these hopes, and isolated communist parties and their members. By analysing the accounts of communist children, Weesjes highlights their struggle to establish communities and define their identities within the specific cultural, social, and political frameworks of the Cold War period and beyond.
Keywords: Children -- Political activity -- Netherlands -- 20th century.; Children -- Political activity -- Great Britain -- 20th century.; Communism -- Netherlands -- 20th century.; Communism -- Great Britain -- 20th century.; Enfance -- Activité politique -- Pays-Bas -- 20e siècle.; Enfance -- Activité politique -- Grande-Bretagne -- 20e siècle.; European history.; The Cold War.; Marxism and Communism.; Political activism.; HISTORY / Europe / General.; HISTORY / Modern / 20th Century.; HISTORY / Social History.; POLITICAL SCIENCE / Political Ideologies / Communism, Post-Communism & Socialism.; Children -- Political activity; Communism; Great Britain; Netherlands; 1900-1999; CPN (Communistische Partij van Nederland), CPGB (Communist Party of Great Britain), identity, childhood, Cold War.